1979
DOI: 10.4141/cjps79-049
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Nitrogen Fertilizer on Nitrogen Fractions and Amino Acid Composition of Spring Wheat

Abstract: InN. lg'7g. Effect of nitrogen fertll\zer on nitrogen fractions and amino acid .composition of spring wheat. Can' J. Plant Grain from hard red spring wheat (Triticum aestivum'Neepawa') grown with nine rares of N fertilizer (0-400 tg/ha) was analyzed for total N, non-protein N (NPN) ' and amino acids. In addition, the amino acid compositions of the various soluble protein fractions were determined. The percent6ges of total N, NPN' and protein The long-term average protein content of Kolderup (1974) 1964… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
8
0

Year Published

1986
1986
2009
2009

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…Protein fractionation was performed by a discontinuous method as summarized in Table 1. Non-Proteic Nitrogen (NPN) was determined on the first fraction (albumins and globulins) after precipitation of the proteins with trichloroacetic acid according to DUBETZ et al (1979). Nitrogen content determinations were made on duplicate samples of each solubility fraction.…”
Section: Methodsmentioning
confidence: 99%
“…Protein fractionation was performed by a discontinuous method as summarized in Table 1. Non-Proteic Nitrogen (NPN) was determined on the first fraction (albumins and globulins) after precipitation of the proteins with trichloroacetic acid according to DUBETZ et al (1979). Nitrogen content determinations were made on duplicate samples of each solubility fraction.…”
Section: Methodsmentioning
confidence: 99%
“…Both protein quantity and quality are required for optimum bread performance. Nitrogen fertilization strongly influences the quantity of protein in wheat flour (Dubetz et al, 1979; Gauer et al, 1992). Studies have demonstrated the importance of N application timing for optimal wheat yield, increased grain protein concentration, and reductions in N loss from the soil‐plant system (Fowler et al, 1989; Hucklesby et al, 1971; Altman et al, 1983; Miezan et al, 1977).…”
mentioning
confidence: 99%
“…Gluten is a composite of two proteins, gliadin and glutenin. Gliadin and glutenin contain tyrosine and histidine 12) that have antioxidant activities 13,14) and are stable even at 120 15) . Meanwhile, the gluten treated with methanol was slightly yellow, indicating that the methanol extraction would be incomplete, and that many components remained in the gluten.…”
mentioning
confidence: 99%